Digital measurement of individual motor and proprioceptive skills in patients with osteoarthritis of the knee prior to total knee replacement - Redelbach, Robert; Mahnke, Alexander; Anders, Jens (Zeitschrift für Orthopädie und Unfallchirurgie, 2020)
Purpose In spite of consistent improvement in operative methods for total knee arthroplasty, individual motor deficits may lead to a lower outcome. The preoperative classification in individual motoric capacity may get more significance for the future. Complementary to established questionnaires and clinical tests, this pilot study should demonstrate that it is possible to generate a preoperative motor score using a force platform measurement (KMP). Compared to questionnaires the new score represents digital values suitable for everyday clinical use. Methods In total 63 Patients were randomized selected on the day before a bicondylar total knee replacement. A mobile force platform KMP (Motosana) measured the parameter maximum force, power and balance. Fluctuation area was measured in mm and fluctuation path in mm. One leg standing without holding, transient help or permanent holding at armrests were registered. The force (Newton) was measured while a modified cross lift exercise and power (Watt) by performing five squads. Results Based on comprehensive statistical consolidated data of maximum force, power and balance it was possible to create a new motor score Knie Fit 1.0. Depending on interindividual performance patients were divided into those with higher or lower results. Regarding to their individual motor proprioceptive capacity we could also graduate patients into 4 different groups for force/power and balance. In total 17 of 63 patients offered a complex motor deficit, but on the other hand 17 different patients showed superior results in all categories. Conclusion It is possible to measure the motor capacity of patients using the mobile force platform (KMP) in everyday clinical practice. Based on this data a new motor score KnieFit 1.0 was generated and groups of patients with different insufficiencies were created. Further follow-up studies should proof and compare the pre- A nd postoperative outcome in this field. With KnieFit 1.0 it may be possible to create an individual perioperative rehabilitation program for compensation of detected deficits.
CRIS-Team Scopus Importer:2020-10-30
Keywords: Gonarthrosis; Mobile force plate; Motor score kniefit 1.0; Proprioceptive skills